Caminhando rumo ao consumo sustentável: uma investigação sobre a teoria declarada e as práticas das empresas no Brasil e no Reino Unido - Kremer, Joelma (2008)
This dissertation evaluated the existence of a double pattern in the treatment given to the questions that refer to the social responsibility of companies bearing in mind the theory they were based upon, and which is presented in their Internet sites for an audience from Brazil and from the United Kingdom. This study also evaluated the theory in use through the analysis of institutions that perform the assessment of these companies by means of socio-environmental indicators and boycott sites. The technical background for this study as well as the discussion of concepts focused on consumption, social movements and sustainable development. The research stresses the fact that we live in a consumption society whose main social partners are the companies and the citizens as consumption entities, what has hindered the organization of social movements that could have been the agents of transformation towards responsible consumption that led to sustainable consumption and therefore to the so called sustainable development, which was the focus of discussions in the 1960s and being widely disseminated by media right now, when issues of global warming, ecological catastrophes and biodiversity threats are being highly debated. The role played by governments with their ruling mechanisms cannot be ignored and civil society organized into social movements or NGO s (Non Governmental Organizations) plays a deeper influence onto these organizations than onto companies, also considering that companies, in turn, act more by coercion than by their own initiative as far as external links are concerned. A significative amount of companies does not make reference neither to their social responsibility nor do they present educational programs capable of improving the way people consume. The double pattern was shown to be less disperse from what was initially forseen, however, based on the data gathered for the study, it is not possible to establish, for most of the companies studied, if there is a link between the theory referred and the theory in use